2016
DOI: 10.3109/00365513.2015.1129670
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory and endothelial markers during the menstrual cycle

Abstract: Background The menstrual cycle exhibits a pattern of repeated inflammatory activity. The present study aims to evaluate inflammatory and endothelial markers during the two phases of a menstrual cycle. Methods The study cohort consisted of 102 women with regular menstrual cycles. Inflammatory and endothelial markers (interleukin-6 [IL-6], pentraxin-3 [PTX-3], hs-C reactive protein [hs-CRP], sE-selectin, sP-selectin, intracellular and vascular cell adhesion molecules [ICAM-1 and VCAM-1] and cathepsins L, B and S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 24 publications
(35 reference statements)
1
21
0
Order By: Relevance
“…Hence, it is possible that both the complexity of the inflammatory response to concussion as well as potentially divergent responses in males and females contribute to these mixed findings. In addition, it is conceivable that the menstrual cycle may have had an effect; immune function can vary widely with hormonal changes during the menstrual cycle, with potential immunosuppression in the luteal phase [35][36][37]. While it is still unclear why we observed that symptom burden was correlated with lower levels of inflammatory cytokines in females following SRC, the results of this investigation provide supportive evidence that inflammation following concussion should not be looked at without dichotomizing groups by sex.…”
Section: Discussionsupporting
confidence: 54%
“…Hence, it is possible that both the complexity of the inflammatory response to concussion as well as potentially divergent responses in males and females contribute to these mixed findings. In addition, it is conceivable that the menstrual cycle may have had an effect; immune function can vary widely with hormonal changes during the menstrual cycle, with potential immunosuppression in the luteal phase [35][36][37]. While it is still unclear why we observed that symptom burden was correlated with lower levels of inflammatory cytokines in females following SRC, the results of this investigation provide supportive evidence that inflammation following concussion should not be looked at without dichotomizing groups by sex.…”
Section: Discussionsupporting
confidence: 54%
“…FM being a chronic condition, it is important to ponder the potential side effects of long-term NSAID use 51. Most FM patients being women, the possible relationship between inflammation and levels of ovarian hormones in FM patients is also a possible area for future investigations 5254…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the number and complexity of the variables [age, phase of the menstrual cycle (follicular/luteal phase), recent pregnancies and breast-feeding, menopause, hormone medications, etc.] which influence the fluctuation of inflammatory parameters probably require an ad hoc study (50). Nevertheless, by SEM analysis, our work provides new evidence of inflammation as a possible pathway linking irregular nocturnal working hours and morbidity.…”
Section: Discussionmentioning
confidence: 99%